Expanding access to non-communicable disease care in rural Malawi: outcomes from a retrospective cohort in an integrated NCD–HIV model - Gene Bukhman; Luckson Dullie; Emily B Wroe; Elizabeth L Dunbar; Noel Kalanga; Lawrence Nazimera; Natalie F Price; Adarsh Shah; Bright Mailosi; Grant Gonani; Enoch P L Ndarama; George C Talama; et al. (BMJ Open)
Objectives Non-communicable diseases (NCDs) account for one-third of disability-adjusted life years in Malawi, and access to care is exceptionally limited. Integrated services with HIV are widely recommended, but few examples exist globally. We report descriptive outcomes from an Integrated Chronic Care Clinic (IC3).Design This is a retrospective cohort study.Setting The study includes an HIV–NCD clinic across 14 primary care facilities in the rural district of Neno, Malawi.Participants All new patients, including 6233 HIV–NCD diagnoses, enrolled between January 2015 and December 2017 were included. This included 3334 patients with HIV (59.7% women) and 2990 patients with NCD (67.3% women), 10% overall under age 15 years.Interventions Patients were seen at their nearest health centre, with a hospital team visiting routinely to reinforce staffing. Data were collected on paper forms and entered into an electronic medical record.Primary and secondary outcome measures Routine clinical measurements are reported at 1-year post-enrolment for patients with more than one visit. One-year retention is reported by diagnosis.Results NCD diagnoses were 1693 hypertension, 668 asthma, 486 epilepsy, 149 diabetes and 109 severe mental illness. By December 2018, 8.3% of patients with NCD over 15 years were also on HIV treatment. One-year retention was 85% for HIV and 72% for NCDs, with default in 8.4% and 25.5% and deaths in 4.0% and 1.4%, respectively. Clinical outcomes showed statistically significant improvement for hypertension, diabetes, asthma and epilepsy. Of the 1807 (80%) of patients with HIV with viral load results, 85% had undetectable viral load.Conclusions The IC3 model, built on an HIV platform, facilitated rapid decentralisation and access to NCD services in rural Malawi. Clinical outcomes and retention in care are favourable, suggesting that integration of chronic disease care at the primary care level poses a way forward for the large dual burden of HIV and chronic NCDs.